Quadratic formula

kristier26

New member
Joined
Dec 11, 2008
Messages
4
3x^2- 5x=13

I know that I must now insert into quadratic formula as follows. a=1 b=5 c=13

-5+/-sqrt -5^2-4 (1)(13)
--------------------
2(1) now my book says to simplify but there example makes it diffiuclt to understand exactly what they are doing. Do I take the -5 squared which is 25 and
-4 (1) (13) which is -52 then 25-52=-27? I feel Im missing something important!
 


a, b, and c are when the equation is set to zero.

ax^2 + bx + c = 0

Put your equation in that form, first.

Then start over with the correct values of a, b, and c.

(You got them all wrong! Look carefully at both the numbers and their signs.)

 
Oh, i was trying to skip a step to save time. The original looked like this..3x^2-5x-13=0. I rewrote it to the other form. so now I see that a=3 b=-5 and c=13. so,

-5=/- sqrt -5^2-4(3)(13)
----------------------------
2(3) Do i Do I take the -5 squared which is 25 and -4 (3) (13) which is -156 then 25-156=-131? or is that all wrong?
 
kristier26 said:
... 3x^2 - 5x - 13 = 0 ... now I see that a = 3, b = -5, and c = 13 ...


-5 +/- sqrt[ (-5)^2 - 4(3)(13) ]
------------------------------------
2(3)


Correct the three errors highlighted in red above.

Then you'll end up with a sum inside the radical sign, instead of a difference.

Other than those three mistakes, you seem to be on the right track. Continue simplifying.

 
Top